Skip to main content
Solve for x, y
Tick mark Image
Graph

Similar Problems from Web Search

Share

3x+7y=63,2x+4y=38
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
3x+7y=63
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
3x=-7y+63
Subtract 7y from both sides of the equation.
x=\frac{1}{3}\left(-7y+63\right)
Divide both sides by 3.
x=-\frac{7}{3}y+21
Multiply \frac{1}{3} times -7y+63.
2\left(-\frac{7}{3}y+21\right)+4y=38
Substitute -\frac{7y}{3}+21 for x in the other equation, 2x+4y=38.
-\frac{14}{3}y+42+4y=38
Multiply 2 times -\frac{7y}{3}+21.
-\frac{2}{3}y+42=38
Add -\frac{14y}{3} to 4y.
-\frac{2}{3}y=-4
Subtract 42 from both sides of the equation.
y=6
Divide both sides of the equation by -\frac{2}{3}, which is the same as multiplying both sides by the reciprocal of the fraction.
x=-\frac{7}{3}\times 6+21
Substitute 6 for y in x=-\frac{7}{3}y+21. Because the resulting equation contains only one variable, you can solve for x directly.
x=-14+21
Multiply -\frac{7}{3} times 6.
x=7
Add 21 to -14.
x=7,y=6
The system is now solved.
3x+7y=63,2x+4y=38
Put the equations in standard form and then use matrices to solve the system of equations.
\left(\begin{matrix}3&7\\2&4\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}63\\38\end{matrix}\right)
Write the equations in matrix form.
inverse(\left(\begin{matrix}3&7\\2&4\end{matrix}\right))\left(\begin{matrix}3&7\\2&4\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&7\\2&4\end{matrix}\right))\left(\begin{matrix}63\\38\end{matrix}\right)
Left multiply the equation by the inverse matrix of \left(\begin{matrix}3&7\\2&4\end{matrix}\right).
\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&7\\2&4\end{matrix}\right))\left(\begin{matrix}63\\38\end{matrix}\right)
The product of a matrix and its inverse is the identity matrix.
\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&7\\2&4\end{matrix}\right))\left(\begin{matrix}63\\38\end{matrix}\right)
Multiply the matrices on the left hand side of the equal sign.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{4}{3\times 4-7\times 2}&-\frac{7}{3\times 4-7\times 2}\\-\frac{2}{3\times 4-7\times 2}&\frac{3}{3\times 4-7\times 2}\end{matrix}\right)\left(\begin{matrix}63\\38\end{matrix}\right)
For the 2\times 2 matrix \left(\begin{matrix}a&b\\c&d\end{matrix}\right), the inverse matrix is \left(\begin{matrix}\frac{d}{ad-bc}&\frac{-b}{ad-bc}\\\frac{-c}{ad-bc}&\frac{a}{ad-bc}\end{matrix}\right), so the matrix equation can be rewritten as a matrix multiplication problem.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-2&\frac{7}{2}\\1&-\frac{3}{2}\end{matrix}\right)\left(\begin{matrix}63\\38\end{matrix}\right)
Do the arithmetic.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-2\times 63+\frac{7}{2}\times 38\\63-\frac{3}{2}\times 38\end{matrix}\right)
Multiply the matrices.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}7\\6\end{matrix}\right)
Do the arithmetic.
x=7,y=6
Extract the matrix elements x and y.
3x+7y=63,2x+4y=38
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
2\times 3x+2\times 7y=2\times 63,3\times 2x+3\times 4y=3\times 38
To make 3x and 2x equal, multiply all terms on each side of the first equation by 2 and all terms on each side of the second by 3.
6x+14y=126,6x+12y=114
Simplify.
6x-6x+14y-12y=126-114
Subtract 6x+12y=114 from 6x+14y=126 by subtracting like terms on each side of the equal sign.
14y-12y=126-114
Add 6x to -6x. Terms 6x and -6x cancel out, leaving an equation with only one variable that can be solved.
2y=126-114
Add 14y to -12y.
2y=12
Add 126 to -114.
y=6
Divide both sides by 2.
2x+4\times 6=38
Substitute 6 for y in 2x+4y=38. Because the resulting equation contains only one variable, you can solve for x directly.
2x+24=38
Multiply 4 times 6.
2x=14
Subtract 24 from both sides of the equation.
x=7
Divide both sides by 2.
x=7,y=6
The system is now solved.